Associations of harsh, unpredictable environment, amygdala connectivity and overeating for children - Luo, Yijun; Chen, Ximei; Zeng, Weiyu; Xiao, Mingyue; Liu, Yong; Gao, Xiao; Chen, Hong (Progress in neuro-psychopharmacology & biological psychiatry, 2023)
In harsh and unpredictable environments, individuals tend to engage in activities that yield immediate rewards as delayed benefits can be unavailable. Substantial evidence suggests that a harsh and unpredictable childhood environment is associated with overeating. However, the neuromechanisms underlying this association remain unclear. This study aimed to investigate amygdala connectivity in relation to environmental harshness and unpredictability (EHU) from an evolutionary perspective and examine their relationship with overeating in children. Eighty-five children aged 8 to 12 years were scanned using a magnetic resonance imaging machine to assess resting-state functional connectivity (RSFC) of the two subregions of the amygdala (i.e., centromedial amygdala [CMA]; basolateral amygdala [BLA]). Self-reports of EHU and parental reports of overeating, including food responsiveness and enjoyment of food, were obtained cross-sectionally. Furthermore, findings indicated that children completed high- and low-calorie food portion choice tasks in the absence of hunger at 12 months of follow-up. EHU was positively associated with parental reports of overeating, including food responsiveness and enjoyment, as well as children's selection of high-calorie food portion sizes. Moreover, static RSFC analyses revealed that EHU was negatively associated with bilateral BLA-left inferior frontal gyrus (IFG) connectivity, while dynamic RSFC analyses found that EHU was negatively associated with right CMA, left inferior parietal lobule, and right CMA-right precuneus connectivity. Particularly, the left BLA-left IFG connectivity mediated the association between EHU and parental reports of food responsiveness. EHU was negatively associated with amygdala connectivity, which is implicated in the intrinsic processing of emotional regulation. Furthermore, deficits in emotional regulation resulted in increased energy intake. These insights provide a new perspective for understanding the developmental neuromechanisms underlying obesity. •Self-report of EHU is associated with parental reports of overeating for children.•EHU is associated with bilateral BLA- left IFG connectivity.•EHU is associated with right CMA-left IPL, right CMA-right precuneus connectivity.•Left BLA-left IFG connectivity mediates the relation of EHU and food responsiveness.